2023
DOI: 10.1097/md.0000000000033573
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy analysis of virtual reality-based training for activities of daily living and functional task training in stroke patients: A single-subject study

Abstract: Introduction: Virtual reality (VR)-based training for functions such as cognition, upper extremities, balancing, and activities of daily living (ADL) has been used on stroke patients, and its efficacy has been reported. However, no comparison has been made between the efficacy of VR-based training for daily activities that exactly reproduces ADL and functional training. Therefore, this study sought to analyze the difference in independency enhancement of VR-based training for daily activities compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…[35] Lee et al (2023) indicated increased improvement in ADL (8.32%) in 4 patients with hemiplegic stroke. [36] By applying audiovisual feedback on deep learning-based rehabilitation, the patients are able to self-train balance deficits by analyzing the postural and balance control suggestions shown in the virtual environment. DRA is a low-cost, portable tool that can be integrated into the rehabilitation plan of post-CP and neurological patients, such as those with traumatic brain injury and stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35] Lee et al (2023) indicated increased improvement in ADL (8.32%) in 4 patients with hemiplegic stroke. [36] By applying audiovisual feedback on deep learning-based rehabilitation, the patients are able to self-train balance deficits by analyzing the postural and balance control suggestions shown in the virtual environment. DRA is a low-cost, portable tool that can be integrated into the rehabilitation plan of post-CP and neurological patients, such as those with traumatic brain injury and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Such rehabilitation frequently requires sophisticated and costly equipment that is only available in hospitals or other specialized facilities. [36,37] DRA not only provides easy and affordable virtual treatment options, but also exhibits positive outcomes in the ongoing recovery of chronic CP survivors.…”
Section: Discussionmentioning
confidence: 99%